IMPLEMENTASI PELAKSANAAN E-PROCUREMENT DENGAN PRINSIP-PRINSIP GOOD GOVERNANCE DI DINAS BINA MARGA PROVINSI JAWA TENGAH - Rizky Adrian; Dyah Lituhayu; Titik Djumiarti (Journal of Public Policy and Management Review, 2013)
E-Procurement is a process of procuring goods / services that are implemented using information technology according to statutory provisions. E-Procurement emerged as the answer to the case of corruption in the implementation of procuring goods and services in Indonesia. The existence of E-Procurement become an interesting phenomenon because the implementation is different from conventional procurement. E-Procurement are expected to answer the expectations of society in order to create a process for of procurement of goods and services that are accountable, transparent, effective and efficient. Based on the regulation No. 11 Year 2008 regarding Information and Electronic Transactions which explains that utilization of information technology was instrumental in trade and growth in the national economy for the welfare of the community, the Department of Highways of Central Java Province implementing E-Procurement since 2009. In its implementation, it was found some problems and obstacles. The problems that arise such as denial and resistance where the service provider are more comfortable to conventional procuring process.